Cancer of the oesophagus and gastroesophageal junction – a difficult clinical problem - Głuszek, Stanisław; Kot, Marta; Kotucha, Bartłomiej; Stępień, Renata; Kozieł, Dorota (Contemporary Oncology/Współczesna Onkologia, 2014)
Introduction: Cancer located in the oesophagus and gastroesophageal junction is a complex clinical problem and the results of its treatment still remain unsatisfactory. The objective of the study was the clinical analysis of a group of patients with cancer of the oesophagus or gastroesophageal junction, who received combined medical and surgical treatment. Material and methods: The analysis was performed on a group of 128 patients with the diagnosis of oesophageal cancer or cancer of the gastroesophageal junction. Analysis of medical records and follow-up examinations were used in the research procedure. Results : From among 128 patients with a diagnosis of oesophageal or gastroesophageal junction cancer, 50 (38.5%) received surgical resections. The surgery most frequently performed (n = 15) was sub-total oesophageal resection according to Akiyama procedure by right-sided thoracotomy (oesophageal anastomosis in the neck). The largest group were patients (n = 26) with stage T 3 N 1 M 0 of advancement of the disease. In all cases of cancer located in the lower third of the oesophagus, an adenocarcinoma pattern was diagnosed in the histopathological examination, whereas in the case of cancers located in the middle third and upper third of the thoracic oesophagus a carcinoma planoepitheliale pattern was seen. Anastomotic leaks occurred in seven patients (14%). Six patients died during the post-operative period (12%). The mean survival time in the group of analysed patients was two years. Conclusions : Cancer of the oesophagus or gastroesophageal junction is associated with low resectability, high risk of complications after surgery, and poor oncologic outcome. It is necessary to seek new methods of treatment.